Support for making Pauline henotic unity the fulcrum of Christian ecumenism in Nigeria - Peters, Prince E. (HTS teologiese studies, 2021)
Paul uses the word ἑνότης twice in Ephesians (4:3, 13), and quite strangely, those are the only two places where the feminine noun features in the whole of the New Testament. In the two passages where they appear, they both relate to invisible unity, the unity of the Spirit that produces a common faith and knowledge of the Son of God – εἰς τὴν ἑνότητα τῆς πίστεως καὶ τῆς ἐπιγνώσεως τοῦ υἱοῦ τοῦ Θεοῦ. Such unity suggests that ecumenism amongst Christian denominations is not only a possibility, it is also a necessity as far as we all profess one Christ. This unity is however far from ecclesiological unionism. Considering that the church appears weak from the outside when its diverse lines of doctrine, sacraments and ministerial ethics are emphasised. This suggests that a reasonable antidote would be the emphasis on the philosophy of unity amidst our diversity especially to the hearing of non-Christians.Contribution: This study makes firm the belief that Christianity is formed on divergent traditions that produced various strands of practices, which in turn produce different Christian sects and denominations, and a reverse is not possible. It then suggests a bonding in faith through the invisibility of henotic unity, which the pericope suggests. This will help the church to amass a stronger defence politically and structurally against rival religions and social organisations even in the midst of doctrinal differences.